Osteoblast‐Derived ECM1 Promotes Anti‐Androgen Resistance in Bone Metastatic Prostate Cancer - Xinwen Wang; Min Wang; Qijun Lin; Lixin He; Baolin Zhang; Xin Chen; Guanhong Chen; Hong Du; Chuandong Lang; Xinsheng Peng; Yuhu Dai (Advanced Science)
Abstract Acquired resistance to hormonal therapy, particularly enzalutamide (ENZ), remains a significant obstacle in the treatment of advanced bone metastatic prostate cancer. Here, it is demonstrated that under ENZ treatment, osteoblasts in the bone microenvironment secrete increased levels of extracellular matrix protein 1 (ECM1), which affects surrounding prostate cancer cells, promoting tumor cell proliferation and anti‐androgen resistance. Mechanistically, ECM1 interacts with the enolase 1 (ENO1) receptor on the prostate cancer cell membrane, leading to its phosphorylation at the Y189 site. This event further recruits adapter proteins including growth factor receptor‐bound protein 2 (GRB2) and son of sevenless homolog 1 (SOS1), which activates the downstream mitogen‐activated protein kinase (MAPK) signaling pathway to induce anti‐androgen resistance. Furthermore, inhibiting ECM1 or utilizing the ENO1‐targeting inhibitor phosphonoacetohydroxamate (PhAH) significantly restores tumor cell sensitivity to ENZ. Taken together, a potential mechanism is identified through which osteoblast‐derived ECM1 drives resistance in bone metastatic prostate cancer under ENZ treatment. Additionally, the findings indicate that ECM1 and ENO1 may serve as potential targets for developing therapies for bone metastatic castration‐resistant prostate cancer.